eCM 2013
DOI: 10.22203/ecm.v025a23
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration of biochemically modified implants in an osteoporosis rodent model

Abstract: The present study examined the impact of implant surface modifications on osseointegration in an osteoporotic rodent model. Sandblasted, acid-etched titanium implants were either used directly (control) or were further modified by surface conditioning with NaOH or by coating with one of the following active agents: collagen/chondroitin sulphate, simvastatin, or zoledronic acid. Control and modified implants were inserted into the proximal tibia of aged ovariectomised (OVX) osteoporotic rats (n = 32/group). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 55 publications
1
69
0
Order By: Relevance
“…6 Yet another surface modification to further stimulate osseointegration is the coating of implant surfaces with biological components. [7][8][9] For bone, these may be organic as well as inorganic in nature, and both can potentially influence cellular activity during periimplant healing. In this context, many different types of surface coatings have been analyzed in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…6 Yet another surface modification to further stimulate osseointegration is the coating of implant surfaces with biological components. [7][8][9] For bone, these may be organic as well as inorganic in nature, and both can potentially influence cellular activity during periimplant healing. In this context, many different types of surface coatings have been analyzed in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…39 Anesthesia was initialized with Isoflurane (Forane ® ; Abbott Laboratories, Abbott Park, IL, USA) with subsequent intramuscular administration of Ketaminol (Ketamin ® ; Dr E Graeub AG, Bern, Switzerland; 100 mg/kg body weight) and Xylasol (Xylazin ® ; Dr E Graeub AG; 10 mg/kg body weight) to assure sufficient narcosis. An overview of the surgical procedure is shown in Figure 2.…”
mentioning
confidence: 99%
“…biphosphonates) or anabolic agents (i.e. parathyroid hormone or bone morphogenetic protein) immobilised on the material surface in the osteoporotic condition, but, to the best of the authors' knowledge, few published papers have evaluated material surface functionalisation with collagen type I in an osteoporotic animal model [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…study design, site of implant, age of the animal, experimental times, different techniques employed to modify material surfaces both topographically than biochemically) are important variables that can influence the results. For example, Stadlinger et al [22] found no detectable impact on the osteointegration parameter (BIC, BI and BV/TV and pull-out test) exerted by a collagen/chondroitin sulphate titanium coating at either two or four weeks after implant. In another in vivo study, Alghamdi et al [21] compared a CaP and collagen type I coated Ti implant to an uncoated one both in healthy and osteoporotic conditions, by adopting a similar experimental set up.…”
Section: Discussionmentioning
confidence: 99%